STRUKTUR GENETIK DAN RAGAM ALEL TIGA GENERASI MASYARAKAT BALI BERDASAR LIMA LOKUS PENANDA DNA MIKROSATELIT AUTOSOM - Laksmita, Ayu Saka; Junitha, I Ketut; Watiniasih, Ni Luh (Metamorfosa: Journal of Biological Sciences, 2015)
This research was aimed to find out the genetic structures of three generations of Balinese population, in order to determine the best loci used for paternity testing among this population, and observed the mutation rate of these loci. The DNA samples were taken from the epithelium cell of 25 families which were collected from the children, father, mother, grandfather and grandmother of the children, from both mother and father sides (family with three generations). The DNA was extracted in Phenol-Chloroform method with modifications. DNA amplification was conducted in PCR method using pairs of primer 5, namely: FGA, D18S51, D2S1338, TPOX, and D16S539, and its products were electrophoresed and visualized in 10% of PAGE, stained in silver nitrate. The genetic structures of the three family generations showed 30 variants with different frequencies in each locus. The highest heterozygosity value was detected in FGA (8 alleles), then followed by D18S51 (7 alleles), TPOX (6 alleles), D16S539 (5 alleles), and the lowest was in D2S1338 (4 alleles). The highest value of heterozigosity and Power of Discrimination were found in FGA, followed by TPOX, D18S51, D2S1338, and the lowest was in D16S539. Therefore, it can be concluded that out of five loci tested, 4 of them can be recommended to be used for paternity testing of Balinese population, except D16S539. Keywords : Paternity Testing, DNA Microsatellite, three generations, heterozygosity, Power of Discrimination
Keywords: Paternity Testing, DNA Microsatellite, three generations, heterozygosity, Power of Discrimination